Estrogen and progesterone receptor subtype expression in granulosa cells from women with polycystic ovary syndrome. (May 2015) - Artimani, Tayebeh; Saidijam, Massoud; Aflatoonian, Reza; Amiri, Iraj; Ashrafi, Mahnaz; Shabab, Nooshin; Mohammadpour, Nooshin; Mehdizadeh, Mehdi
Abstract We evaluated gene expression of estrogen and progesterone nuclear receptors in granulosa cells (GCs) of polycystic ovary syndrome (PCOS) women compared to women with normal cycling ovaries (control group) to achieve a better understanding of ovarian steroid status in patients with PCOS. In this prospective study, 40 patients with PCOS and 40 women with normal ovulatory function who underwent in vitro fertilization (IVF) for treatment of tubal and/or male infertility were recruited. Follicular fluid was collected from patients and GCs were isolated from follicular fluid and then were purified with Micro Beads conjugated to monoclonal anti-human CD45 antibodies. RNA was extracted and reverse transcription was performed. Gene expression of estrogen and progesterone receptors was determined by quantitative real time PCR (qRT-PCR). Estrogen receptor β (ERβ) expression was significantly higher than ERα expression in both groups (p < 0.002). ERα and ERβ mRNA expression in PCOS was significantly lower than control group (p < 0.002). The expression levels of PRA and PRB in PCOS was significantly lower than control group (p < 0.002). In conclusion, a significant reduction of these genes in GCs from follicles of women with PCOS could be considered as a sign for maturation defect or follicular arrest in GCs.